ANALISIS PENGARUH EFEKTIVITAS DAN KONTRIBUSI PENERAPAN PERATURAN PEMERINTAH NOMOR 46 TAHUN 2013 TERHADAP PENERIMAAN PAJAK PADA KANTOR PELAYANAN PAJAK DI PULAU LOMBOK - I Made Suardana; Ni Nyoman Yuliati; Randy Randy (Valid: Jurnal Ilmiah, 2018)
This study aims to examine the effect of the effectiveness and contribution of the implementation of government regulation number 46 year 2013 on tax revenue in the tax service office on the Lombok island. Penelitian using a quantitative approach, where the subject of research focused on the tax office on the Lombok island. Data analysis in this research use multiple regression.The resulting model and significance test found that the level of effectiveness and contribution rate of application of Government Regulation no. 46 year 2013 partially and simultaneously have a significant influence on tax revenue in three tax offices on the Lombok island.